2023
DOI: 10.3390/diagnostics13111849
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Liquid Colony™ Produced by the FAST System for Shortening the Time of Bacterial Identification and Phenotypic Antimicrobial Susceptibility Testing and Detection of Resistance Mechanisms from Positive Blood Cultures

Abstract: Background: the aim of this study was to evaluate the performance of the Liquid Colony™ (LC) generated directly from positive blood cultures (PBCs) by the FAST System (Qvella, Richmond Hill, ON, Canada) for rapid identification (ID) and antimicrobial susceptibility testing (AST) compared with the standard of care (SOC) workflow. Methods: Anonymized PBCs were processed in parallel by the FAST System and FAST PBC Prep cartridge (35 min runtime) and SOC. ID was performed by MALDI-ToF mass spectrometry (Bruker, Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Intended for automated processing of blood culture specimens, the FAST system has yielded promising results in early studies to support clinical use when paired with various downstream identification and AST platforms [13][14][15][16][17]. Prospective studies have found that for positive blood cultures, FAST system processing can be used to rapidly obtain correct organism identifications by MALDI-TOF in 87-96 % of cases, and AST results with ~98 % categorical agreement with standard of care AST [13][14][15][16][17][18]. Not only has the FAST system been shown to be highly accurate, it has also been shown by other studies to significantly reduce workflow time [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intended for automated processing of blood culture specimens, the FAST system has yielded promising results in early studies to support clinical use when paired with various downstream identification and AST platforms [13][14][15][16][17]. Prospective studies have found that for positive blood cultures, FAST system processing can be used to rapidly obtain correct organism identifications by MALDI-TOF in 87-96 % of cases, and AST results with ~98 % categorical agreement with standard of care AST [13][14][15][16][17][18]. Not only has the FAST system been shown to be highly accurate, it has also been shown by other studies to significantly reduce workflow time [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies have found that for positive blood cultures, FAST system processing can be used to rapidly obtain correct organism identifications by MALDI-TOF in 87-96 % of cases, and AST results with ~98 % categorical agreement with standard of care AST [13][14][15][16][17][18]. Not only has the FAST system been shown to be highly accurate, it has also been shown by other studies to significantly reduce workflow time [17,18].…”
Section: Discussionmentioning
confidence: 99%